Inflammatory abrasion of hematopoietic stem cells: a candidate clue for the post-CAR-T hematotoxicity? - Sun, Ting; Li, Dengju; Huang, Liang; Zhu, Xiaojian (Frontiers in immunology, 2023)
Chimeric antigen receptor T-cell (CAR-T) therapy has shown remarkable effects in treating various hematological malignancies. However, hematotoxicity, specifically neutropenia, thrombocytopenia, and anemia, poses a serious threat to patient prognosis and remains a less focused adverse effect of CAR-T therapy. The mechanism underlying lasting or recurring late-phase hematotoxicity, long after the influence of lymphodepletion therapy and cytokine release syndrome (CRS), remains elusive. In this review, we summarize the current clinical studies on CAR-T late hematotoxicity to clarify its definition, incidence, characteristics, risk factors, and interventions. Owing to the effectiveness of transfusing hematopoietic stem cells (HSCs) in rescuing severe CAR-T late hematotoxicity and the unignorable role of inflammation in CAR-T therapy, this review also discusses possible mechanisms of the harmful influence of inflammation on HSCs, including inflammatory abrasion of the number and the function of HSCs. We also discuss chronic and acute inflammation. Cytokines, cellular immunity, and niche factors likely to be disturbed in CAR-T therapy are highlighted factors with possible contributions to post-CAR-T hematotoxicity.